2022
DOI: 10.1186/s40795-022-00501-2
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and associated factors among 6–23 month old children in drought vulnerable kebeles of Demba Gofa district, southern Ethiopia

Abstract: Background Stunting is impaired linear growth of children: they experience stunting in the first 1000 days after conception and is an indication of chronic malnutrition. Children under the age of two are regarded as the most vulnerable to malnutrition due to their rapid growth and greater exposure to infectious disease. Objective To assess the magnitude and associated factors of stunting among 6 to 23-month-old children in drought-vulnerable kebele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Specifically, having less than five children aged below five years in a household was shown to be a significant predictor for good nutrition status even after adjusting for other confounders at multivariable analysis. Similar findings were reported in Ethiopia [ 18 ], Pakistan [ 31 ] and Malaysia [ 32 ]. In Ethiopia, children from households with less than three under-five children were about 4.5 times less likely to be undernourished (underweight) as compared to their counterparts from households with three or more children under-five (AOR = 4.52; 95% CI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Specifically, having less than five children aged below five years in a household was shown to be a significant predictor for good nutrition status even after adjusting for other confounders at multivariable analysis. Similar findings were reported in Ethiopia [ 18 ], Pakistan [ 31 ] and Malaysia [ 32 ]. In Ethiopia, children from households with less than three under-five children were about 4.5 times less likely to be undernourished (underweight) as compared to their counterparts from households with three or more children under-five (AOR = 4.52; 95% CI.…”
Section: Discussionsupporting
confidence: 90%
“…Use of any family planning method by mothers was also significantly associated with the child’s optimal nutrition status. A similar study in Ethiopia [ 18 ] showed that a child whose mother was not using family planning was about 2.5 times more likely to be stunted as compared to those who used family planning (AOR = 2.54 95% CI. 1.12–5.77).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Ethiopia, malnutrition contributes more than 50 percent of all infant and child deaths 8 , and according to the recent 2019 Ethiopian mini Demographic and Health Survey (EMDHS), the prevalence of stunting (37%), wasting (7%) and underweight (21%) was unacceptably high 13 . Moreover, existing primary studies in different parts of the country have reported high burden of undernutrition in children aged 0–23 months- with prevalence of stunting (21.8%-42⋅7%) 11 , 14 – 16 , wasting (9.9%-11.6%) 16 , and underweight (27.7%) 16 . Ethiopia as a nation is still dealing with a number of underlying vulnerabilities for childhood malnutrition, including food insecurity 17 , 18 , caused by multifactorial determinants such as prolonged drought and famine, poverty and civil unrest 19 21 .…”
Section: Introductionmentioning
confidence: 99%